2022
DOI: 10.1002/btm2.10410
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the detection performance of severe acute respiratory syndrome coronavirus 2 test through a sensitive optical biosensor with new superior antibody

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) virus emerged in late 2019 leading to the COVID‐19 disease pandemic that triggered socioeconomic turmoil worldwide. A precise, prompt, and affordable diagnostic assay is essential for the detection of SARS‐CoV‐2 as well as its variants. Antibody against SARS‐CoV‐2 spike (S) protein was reported as a suitable strategy for therapy and diagnosis of COVID‐19. We, therefore, developed a quick and precise phase‐sensitive surface plasmon resonance (PS‐S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
(157 reference statements)
0
4
0
Order By: Relevance
“…After that, the capture antibody, anti-S pAb, at a concentration of 30 μg/mL was covalently immobilized onto the chip surface using the standard amine coupling procedure. The anti-S pAb was produced as described in a previous study and displayed a high binding affinity against the SARS-CoV-2 spike protein of about K D = 7.49 nM . The amine coupling kit was purchased from Cytiva (Marlborough, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, the capture antibody, anti-S pAb, at a concentration of 30 μg/mL was covalently immobilized onto the chip surface using the standard amine coupling procedure. The anti-S pAb was produced as described in a previous study and displayed a high binding affinity against the SARS-CoV-2 spike protein of about K D = 7.49 nM . The amine coupling kit was purchased from Cytiva (Marlborough, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The anti-S pAb was produced as described in a previous study and displayed a high binding affinity against the SARS-CoV-2 spike protein of about K D = 7.49 nM. 28 The amine coupling kit was purchased from Cytiva (Marlborough, USA). All solutions were injected manually with syringes.…”
Section: Methodsmentioning
confidence: 99%
“…Lin et al developed a phasesensitive surface plasmon resonance biosensor for the fast and accurate detection of severe acute respiratory syndrome coronavirus 2. 24 Zheng et al designed a skin patch composing of swellable microneedles and electrochemical test strips to monitor the levels of glucose and alcohol inside the body. 25 Li et al reported a wearable wound dressing system for monitoring wound condition and sepsis-related biomarker procalcitonin in a real-time manner, which showed great potential for early sepsis diagnosis.…”
Section: Disease Diagnosismentioning
confidence: 99%
“…Disease diagnosis involves the detection and quantification of specific biological molecules that are closely related with the presence of a pathogen or the disease progress. Lin et al developed a phase‐sensitive surface plasmon resonance biosensor for the fast and accurate detection of severe acute respiratory syndrome coronavirus 2 24 . Zheng et al designed a skin patch composing of swellable microneedles and electrochemical test strips to monitor the levels of glucose and alcohol inside the body 25 .…”
Section: Disease Diagnosismentioning
confidence: 99%